2020
DOI: 10.3390/ijerph17238780
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterology Procedures Generate Aerosols: An Air Quality Turnover Solution to Mitigate COVID-19’s Propagation Risk

Abstract: The growing fear of virus transmission during the 2019 coronavirus disease (COVID-19) pandemic has called for many scientists to look into the various vehicles of infection, including the potential to travel through aerosols. Few have looked into the issue that gastrointestinal (GI) procedures may produce an abundance of aerosols. The current process of risk management for clinics is to follow a clinic-specific HVAC formula, which is typically calculated once a year and assumes perfect mixing of the air within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…During the pandemic, measures used by endoscopy facilities to prevent exposure during GI endoscopy led to workflow disruptions, mainly with regard to lengthy procedure room turnover times, reductions in procedure capacity, and worsened staff working conditions (ie, implementing new safety protocols, reprocessing facilities, donning and doffing PPE, etc), despite a lack of evidenced-based analysis of the potential for airborne transmission during GI endoscopy. 14 By visualizing endoscopy-generated droplet aerosols, our study helps identify procedures that pose the greatest risk for aerosolization during standard GI endoscopy. These findings can help better inform clinical guidelines on appropriate PPE and other measures for transmission risk mitigation during GI endoscopy while allowing healthcare workers to continue to deliver safe and efficient care.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, measures used by endoscopy facilities to prevent exposure during GI endoscopy led to workflow disruptions, mainly with regard to lengthy procedure room turnover times, reductions in procedure capacity, and worsened staff working conditions (ie, implementing new safety protocols, reprocessing facilities, donning and doffing PPE, etc), despite a lack of evidenced-based analysis of the potential for airborne transmission during GI endoscopy. 14 By visualizing endoscopy-generated droplet aerosols, our study helps identify procedures that pose the greatest risk for aerosolization during standard GI endoscopy. These findings can help better inform clinical guidelines on appropriate PPE and other measures for transmission risk mitigation during GI endoscopy while allowing healthcare workers to continue to deliver safe and efficient care.…”
Section: Discussionmentioning
confidence: 99%
“…Current endoscopic procedures rely on PPE (enhanced during COVID-19), comprehensive room and equipment cleaning and of course air circulation ( Garbey et al, 2020 ) which can vary for endoscopy suites. Despite concerns around patient exposure to the virus due to contaminated endoscopes, evidence suggests that reprocessing agents with viricidal activity will remove the SARS-CoV-2 virus ( Kampf et al, 2020 ; Rai, 2020 ).…”
Section: Impact Of Covid-19 On Flexible Gi Endoscopymentioning
confidence: 99%
“…Apart from that, there is a need for evaluation of mechanical barriers and extractors currently employed in the hospitals to provide best and uniform guidelines for clinicians working during a pandemic. Air filtration is another key aspect in reducing HCW exposure to any potential aerosols ( Garbey et al, 2020 ).…”
Section: Impact Of Covid-19 On Flexible Gi Endoscopymentioning
confidence: 99%
“…Therefore, the importance of air flow was imperative, as it was recognised that post-procedure turnover time or ‘down-time’ was required to let aerosolised particles settle and therefore reduce potential cross-infection. The down-time is dependent on air flow cycles within the procedure room to reduce the particulate burden of air, the procedure type and the Covid status of patient[ 37 ]. Infection control reviews of some units revealed suboptimal air exchange in endoscopy rooms and a lack of infection prevention training in some units.…”
Section: The Effect Of Covid-19 On Gastroenterology and Hepatology Servicesmentioning
confidence: 99%